IL-17/miR-192/IL-17Rs regulatory feedback loop facilitates multiple myeloma progression. - Yuanyuan Sun; Jing Pan; Shudan Mao; Jieping Jin (PLoS ONE, 2014)
Multiple myeloma (MM) is a clonal plasma cell disorder which constitutes the second most common hematological malignancy, and remains an incurable tumor with poor survival. Recently, interleukin-17 (IL-17), produced locally in the tumor microenvironment, has been reported to play a crucial role in tumor immunity. In this study, we determined that exposure of MM cells to IL-17 had various promotive influences on different aspects of tumor progression. IL-17 significantly induced cell proliferation, inhibited cellular apoptosis, repressed cell adhesion to fibronectin and collagen I, and facilitated cell migration. Exposure to IL-17 also resulted in epithelial-mesenchymal transition (EMT), as evidenced by repression of the epithelial marker E-cadherin, and induction of the mesenchymal marker Vimentin, and EMT transcription factors Snail and Slug. Further experiments showed that IL-17 activated the oncogenic p65 transcription factor, which directly repressed the miR-192 gene via binding to the miR-192 promoter. Loss of miR-192 in MM cells can mimic the effects of IL-17, and was required for the above oncogenic effects of IL-17 on MM. Furthermore, we found that miR-192, and its homologous miR-215 directly targeted the 3'-untranslated regions of IL-17Rs, including IL-17RA and RE mRNA. By examining bone marrow specimens derived from MM patients, a negative correlation between miR-192 expression and IL-17 or IL-17RA expression was observed. Also, IL-17 was negatively correlated with E-cadherin and positively with Vimentin. Taken together, our study provides evidence that the IL-17/miR-192/IL-17Rs regulatory feedback loop is manifest in MM and might represent a promising and efficient prognostic marker and therapeutic target for MM.